The Politics of Affect the Glue of Religious and Identity Conflicts in Social Media. - Abdel-Fadil, Mona.
Affect theory often overlooks decades of anthropological, feminist, queer, and postcolonial scholarship on emotion. I build on this extensive scholarship of emotion and use my online ethnography of a Facebook group that promotes the public visibility of Christianity as a springboard to build a conceptual framework of the politics of affect. I address three theoretical gaps: 1) the lack of distinction between different emotions, 2) how affect is often performed for someone, and 3) the varying intensities of emotion. I delve into the intricate ways in which emotions fuel identities, worldviews, and their contestations, and how fake news may come to be perceived as affectively factual. This article deepens our understanding of the role of affect in polemic and mediatized conflicts. The role of emotion in religious conflicts and identity politics is not simply analytically useful, but is, at times, the very fabric of which political ideas are made.
Keywords: Mediatized conflict; Social media; Affect; Politics affect; Religion -- Media -- Digital Culture -- Periodicals; Facebook; Anthropology of emotion; Identity; Nationalism